2016
DOI: 10.1080/19420862.2016.1193660
|View full text |Cite
|
Sign up to set email alerts
|

Utility of a human FcRn transgenic mouse model in drug discovery for early assessment and prediction of human pharmacokinetics of monoclonal antibodies

Abstract: (2016) Utility of a human FcRn transgenic mouse model in drug discovery for early assessment and prediction of human pharmacokinetics of monoclonal antibodies, mAbs, 8:6, 1064-1078, DOI: 10.1080/19420862.2016 To link to this article: https://doi.org/10. 1080/19420862.2016 ABSTRACTTherapeutic antibodies continue to develop as an emerging drug class, with a need for preclinical tools to better predict in vivo characteristics. Transgenic mice expressing human neonatal Fc receptor (hFcRn) have potential as a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
81
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 84 publications
(93 citation statements)
references
References 54 publications
7
81
0
Order By: Relevance
“…The exponents required to predict cynomolgus monkey data to human were in agreement with the literature examples. The hFcRn Tg32 mouse data were encouraging as it predicted well to human, and provides a potential species to replace cynomolgus monkey for human PK predictions of mAbs 23 . Volumes of distribution from central and peripheral compartments in general scaled with an allometric exponent of 1, similar to literature analyses.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…The exponents required to predict cynomolgus monkey data to human were in agreement with the literature examples. The hFcRn Tg32 mouse data were encouraging as it predicted well to human, and provides a potential species to replace cynomolgus monkey for human PK predictions of mAbs 23 . Volumes of distribution from central and peripheral compartments in general scaled with an allometric exponent of 1, similar to literature analyses.…”
Section: Discussionsupporting
confidence: 71%
“…In addition, for a subset of mAbs, PK data were available in transgenic mice expressing the human neonatal Fc receptor (Tg32 homozygous hFcRn mice). The hFcRn Tg32 mouse model was chosen over wild type (WT) mouse because mAb PK is often variable in WT mouse with poor predictability to human, which may be due to species differences in binding of human mAbs to mouse FcRn 22 , 23 . Following cellular uptake of mAbs exhibiting linear CL, FcRn functions as a salvage receptor to protect IgG from rapid intracellular catabolism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, other studies have shown that hFcRn transgenic mice provided numerically superior human clearance predictions compared to wild-type mice. 3,12 A recent publication using a larger cohort of antibodies showed the Tg32 hFcRn strain predicted human clearance within 2-fold for 100% of the molecules evaluated, whereas wild-type mice predicted human clearance within 2-fold for 73% of the molecules evaluated. 12 A YTE engineered mutation in the Fc region of mAbX-YTE was also evaluated in the SCID mouse model and PK properties were compared to mAbX, which is the same molecule without any mutations.…”
Section: Discussionmentioning
confidence: 99%
“…3,12 A recent publication using a larger cohort of antibodies showed the Tg32 hFcRn strain predicted human clearance within 2-fold for 100% of the molecules evaluated, whereas wild-type mice predicted human clearance within 2-fold for 73% of the molecules evaluated. 12 A YTE engineered mutation in the Fc region of mAbX-YTE was also evaluated in the SCID mouse model and PK properties were compared to mAbX, which is the same molecule without any mutations. This mutation increases affinity to the human FcRn receptor and can promote recycling of the antibody instead of subsequent degradation, therefore prolonging exposure and half-life.…”
Section: Discussionmentioning
confidence: 99%